The Effect of Back Massage on Increasing Oxytocin Levels in Breastfeeding Women - Sri Putriani Sinaga; Mufdlilah; Dhesi Ari Astuti (Oksitosin : Jurnal Ilmiah Kebidanan, 2025)
One of the efforts made to facilitate breast milk production is by doing back massage. Back massage is one solution to overcome insufficient breast milk. The purpose of this study was to determine the effect of back massage on increasing oxytocin levels in breastfeeding mothers at TPMB Istri Utami, Yogyakarta. This study used a quantitative method with a quasi-experimental research design with a one-group pretest-posttest design. The population in this study were 30 breastfeeding mothers with normal delivery. The number of samples was 30. The instruments used were observation sheets and questionnaires. There was a difference in increasing oxytocin levels in breastfeeding mothers before and after back massage with the results of the logistic regression test using the F test obtained a sig. value of 0.004 <0.05, and using the t test obtained a sig. value of 0.005 <0.05 with an Exp (B) / OR value of 8,750 having a chance of 8,750 times increasing oxytocin levels after being given treatment (back massage). Value B = Natural Logarithm of 8.750 = 2.558. Back massage has an effect on increasing oxytocin levels in breastfeeding mothers.